Analisis Pengaruh Relationship Marketing terhadap Loyalitas Pelanggan pada PT. Pangkalan Baru Indah Pekanbaru - Yusnita Octafilia; Mira Oktavia (COSTING : Journal of Economic, Business and Accounting, 2018)
Riau is one of the provinces with the largest number of Palm Oil Mill in Indonesia. The large amount of existing Palm Oil Mill and the less amount of customers makes Palm Oil Mill must be able to maintain their business relationship in order to stabilize their selling. The existence of intense competition and the necessity to maintain their business relationship are a phenomenon of this research so the purpose of this study is to analyze the influence of Relationship Marketing Inputs to customer loyalty at PT. Pangkalan Baru Indah Pekanbaru. The research is used questionnaires method on 65 customers of PT. Pangkalan Baru Indah Pekanbaru. Data analysis method on this research is used quantitative analysis which analyzes through statistical calculation using software program SPSS version 19.0. The result of this research shows understanding customer expectation, building service partnership dan total quality management have positive and significant effect to customer loyalty in PT. Pangkalan Baru Indah while empowering employees has no significant effect to customer loyalty of PT. Pangkalan Baru Indah Pekanbaru. Keywords : Relationship Marketing, Understanding Customer Expectation, Building Service Partnership, Total Quality Management, Empowering Employees and Customer Loyalty